Relasi Kuasa Dalam Cerpen Kafanu Al - Ustazi Karya Haifa Bitar : Analisis Kuasa Michel Foucault - Nizar, Mohammad; Pujiharto (PT. Kreasi Karya Majakata, 2023)
This article attempts to reveal the relations of power, resistance and opposition that exist in the short story